Students’ expectations from innovations in education - A. P. Avdeeva; Yu. A. Safonova (Вестник университета)
The article presents the results of a study carried out at Bauman Moscow State Technical University (National Research University) in order to identify students’ expectations regarding the directions of professional education transformation. Based on the results of the analysis of student’s essays, the following priority technologies that students consider innovative were highlighted: 1) developing social competencies, 2) contributing practice-oriented learning, 3) gamification, 4) visualisation (taking into account modern technologies), 5) tutoring (mentoring, coaching). As the main innovation of the last two years, students note distance learning, the distance technologies integration into the traditional educational process. The results of the study may be of interest both to the universities management and to the teaching staff.